It is Not What You Say that Matters But How You Say Itaing the Same Old Song Advertising and Integrated Marketing Communications (Imc) is Manipulative and Deceitful (Global Journal of Management and Business Research, 2013)
When we consider corporate morality we must conclude that no price is too high, for in the long run we have no alternative to ethical business behaviour" Fred. T. Aller.
Keywords: ethics; ethical conducts; law; morality; integrated marketing communications; advertising and promotions